Regulation of Paneth cell-specific genes in COVID-19 patients and SARS-CoV-2-infected mice by quantification of mRNA from exfoliated cells in stool samples - Gill Diamond; Erika L. Figgins; Denny Gao; Tanya O. Robinson; Kenneth Wilson; Jon D. Gabbard; Charles D. Anderson; Lalit Batra; Chithra Sreenivasan; Jian Zheng; Uyen Do; Braden Mulcahy; et al. (Scientific Reports)
Abstract The Paneth cell, a secretory cell of the small intestine, expresses numerous host defense proteins, and is hypothesized to play an important role in host defense against infection. However, studying gene expression in this cell requires invasive procedures. To test the hypothesis that we could observe Paneth cell-specific gene regulation from exfoliated cells in infectious conditions, we obtained stool samples from patients with COVID-19 and uninfected controls. Total mRNA was isolated, and Paneth cell-specific and non-specific gene expression was quantified by RT-PCR. Results revealed a significant decrease in mRNA levels from Paneth cell-specific genes, including DEFA5, DEFA6, PLA2G2A, PRSS2 and ITLN2 in SARS-CoV-2 positive patients compared with controls. Other gut markers, not specific to Paneth cells were unchanged. To validate this experimentally, we infected mice with SARS-CoV-2 and collected fecal pellets over the course of 7 days. We observed a similar time-dependent reduction in Paneth cell-specific transcripts, which correlates with histological changes in the gut. This is the first demonstration of quantification of Paneth cell-specific transcripts without invasive sampling. It also shows the coordinate regulation of these genes as a response to infection with SARS-CoV-2, possibly through viral pathogenesis, to increase infectivity in the gut.